HIV Infection and the Esophagus - Linda Rabeneck (Canadian Journal of Gastroenterology)
The esophagus can be involved in human immune deficiency virus (HIV) infection. Esophageal ulcers can occur as part of an acute (primary) HIV infection syndrome. ln addition. the esophagus can be involved with the neoplasms associated with acquired immune deficiency syndrome (AIDS) – both Kaposi's sarcoma and non-Hodgkin's lymphoma. Opportunistic infections may also involve the esophagus, most commonly candida and cytomegalovirus infection. It is important for gastroenterologists to be aware of the clinical features of these lesions and to be ready to carry out endoscopy to diagnose these lesions correctly.